Enhancing Arabic Vocabulary Mastery Through Virtual Tour Media: A Quasi-Experimental Study at an Integrated Islamic Elementary School - Raihana Nur Azizah; Agus Yasin; Muhammad Ismail (ALSINATUNA, 2025)
Arabic vocabulary (mufrodat) is a foundational element in mastering the Arabic language, especially for elementary students in Islamic education. However, conventional teaching methods and limited media often hinder student engagement and vocabulary retention. This study aimed to evaluate the effectiveness of Virtual Tour–based interactive media in improving students’ Arabic vocabulary mastery. The research employed a quasi-experimental one-group pretest-posttest design involving 28 fifth-grade students at an Integrated Islamic Elementary School in Yogyakarta. Research instruments included classroom observations, teacher interviews, a student motivation questionnaire (10 valid and reliable items), and a vocabulary test (15 valid and reliable items). The results indicated an increase in mean scores from 48.18 to 72.39. The Wilcoxon signed-rank test yielded Z = −3.888 with p < 0.001, indicating a statistically significant improvement. The mean N-Gain score was 0.48, classified as a moderate improvement.  All questionnaire items scored above 4.0 on a five-point Likert scale, with an overall mean of 4.37, categorized as very good. These findings suggest that Virtual Tour media can effectively enhance motivation, interaction, and contextual vocabulary acquisition. The study contributes to the development of digital media in Arabic language education and offers an innovative alternative for Arabic teachers at the elementary level.